Cavity nesting birds show behavioural plasticity to simulated territorial intrusions in response to natural resource pulses - Andrea R. Norris; Kathy Martin (Scientific Reports)
Abstract We investigated the impact of two natural pulses (food and nesting resources) on intra- and inter-specific territorial behaviour of species that co-occur year-round in multi-species groups. We simulated conspecific and heterospecific territorial intrusions in two cavity-nesting species using 974 model presentations with territorial song playbacks during and after a dual resource pulse of insect (bark beetle) prey and nest cavities across 5 years in British Columbia, Canada. As beetle abundance increased, both species increased aggression toward conspecific intruders. At peak beetle abundance the (typically) subordinate generalist insectivore, mountain chickadee (Poecile gambeli), attacked model intruders more frequently than did the dominant bark insectivore, red-breasted nuthatch (Sitta canadensis), and responded more aggressively to nuthatch intruders than to conspecifics. The reversal in the inter-specific dominance hierarchy suggests that behavioural mechanisms governing community structure may change during resource pulses. Overall, we suggest that social interactions between chickadees and nuthatches are dynamic with high complexity and flexibility to major ecological changes. Future work that examines the fitness consequences of temporal variation in community dynamics and resiliency could help to reveal evolutionary mechanisms by which these species co-exist.